Inovasi Pengemasan Produk sebagai Upaya Peningkatan Daya Saing UMKM dalam Program Pengabdian kepada Masyarakat: Product Packaging Innovation as an Effort to Improve MSME Competitiveness in a Community Engagement Program - Mufti, Dessi; Noviyarsi, Noviyarsi; Ulfah, Maria; Burmawi, Burmawi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Micro, small, and medium enterprises (MSMEs) in Indonesia are recognized as playing a critical role in the national economy, yet their competitiveness remains constrained, particularly in product packaging. To address this issue, a community service program was implemented to provide training and mentoring on packaging innovation to MSME actors producing fish sponge cake, keripik saka, papaya serundeng, bareh randang, wajik Bandung, assorted cakes, arai pinang, as well as embroidery and bed cover products. The program was carried out in Kanagarian Simarasok, Baso District, Agam Regency, using a participatory training approach, field observation, and outcome evaluation. The results indicated that, following the intervention, improvements were observed in MSME actors’ understanding of the strategic role of packaging, in the aesthetic and functional quality of packaging, and in consumer interest in their products. Packaging innovation was shown not only to increase visual attractiveness, but also to extend product shelf life and to strengthen a more professional product image. The program was therefore shown to contribute to MSME empowerment in the context of increasingly competitive markets. The training increased participants’ knowledge to 90%, and 14 MSME actors developed new packaging designs for their products.